Efeito de diferentes processamentos domésticos de cocção na retenção ?-caroteno, fenóis totais e na atividade antioxidante da batata doce biofortificada com carotenoides pró-vitamina A - Fornazier, Eduardo Lorencetti (2018)
The sweet potato (Ipomoea batatas (L.) Lam.) Is a source of fiber, carbohydrates, minerals, vitamin C and phytochemical compounds such as carotenoids and phenolic compounds. There are several cultivars containing pro-vitamin A carotenoids at varying concentrations; however, the orange pulp sweet potato species, which has the highest concentrations, is still poorly used and may represent a viable strategy to combat vitamin A deficiency in underdeveloped countries. The Beauregard germplasm was developed through a food biofortification project, whose carotenoid contents are on average 100 times higher than conventional sweet potatoes of white pulp. After cooking, it is known that the carotenoid content in the food can be significantly affected, however different methods can be used for the preparation of the potato and some can help in maintaining the nutritional characteristics. The objective of this study was to evaluate the effect of seven different domestic cooking processes: frying in oil, frying in an electric fryer of the air fryer type, steam cooking in electric pan of the type "rice cooker", cooking by immersion in boiling water, cooking in a pressure cooker, electric oven baking and microwaving under the phenolic compound and antioxidant activity in conventional and biofortified sweet potatoes, and the actual retention of ß-carotene in biofortified sweet potatoes. The centesimal composition and color instrumental analysis were performed on sweet potatoes in natura. Subsequently, the sweet potatoes were peeled, washed and cut in the shape of "toothpick" and cooked in various processes. The experimental design was a factorial and Tukey test (p <0.05) was used to compare the mean values of the analyzed compounds between the treatments and between the types of potatoes. The sweet potato biofortified in natura presented superior concentrations of total phenols and antioxidant activity in relation to the conventional sweet potato. The air fryer and oil frying processes presented the best results for phenolic compounds. The frying methods in oil, electric oven, pressure cooker and air fryer were the best processes in the preservation of antioxidant activity by the DPPH method and air fryer, electric oven and microwave by the method by ABTS. Cookies in pressure cookers (103.26%) and immersion in hot water (93.72%) were identified as the best methods of domestic processing to increase the retention of ß-carotene in biofortified sweet potatoes.